Evaluation in house mesh of the effect of four biological products for the combat of jobotos (Phyllophaga sp.) - Acuña-Segura, Ricardo (2020)
The experiment was developed at home mesh and the effect and dose of four biological products and one chemical used in the control of larvae of jobotos (Phyllophaga sp.) was evaluated. The experiment was carried out in Guadalupe de Cartago, located at the following geographic coordinates: Latitude: 9.861884 and Longitude: -83.939692, at 1400 amsl. The type of research was quantitative with a design of the complete block experiment at random, with the use of two doses and five treatments with three repetitions and each repetition with ten experimental units. The biological products used were: Mycotrol® 11 EW (Beauveria bassiana, strain GHA), Botani Gard® 50 WP (Beauveria bassiana, strain GHA), Agro Gold® (nine strains of Bacillus spp), B-Green® (entomonematode, Heterorhabditis bacteriophora) and a commercial chemical recommended for control of jobotos. For the biological control of Phyllophaga sp., It was determined that Mycotrol® 11EW, was the product for which a dose of 2.25cc / liter of water provided the best results. For the other two products that had an effect on the combat of Phyllophaga sp., Agro Gold® and B-Green®, it was determined that the dose used in both cases was not significant, this is confirmed by the p values of 0.113 and 0.807, respectively. What did have significance was to make two applications of a week between them with these two products. With the remaining products, T2 and T5, there was no statistical significance in their result, this is confirmed by the p value for T2, which for the dose factor was 0.573 and with the application factor was 0.094. For T5 the value of p with the dose factor was 0.260 and for the application factor it was 0.277.